BOOSTING THE SKIN DELIVERY OF CURCUMIN THROUGH STEARIC ACID-ETHYL CELLULOSE BLEND HYBRID NANOCARRIERS-BASED APPROACH FOR MITIGATING PSORIASIS - JAISWAL, PANKAJ KUMAR; DAS, SANJOY; DAS, MALAY K. (International Journal of Applied Pharmaceutics, 2021)
Objective: Curcumin presents poor topical bioavailability when administered orally, which poses a major hurdle in its use as an effective therapy for the management of psoriasis. The present study reports the utilization of lipid-polymer hybrid nanoparticles (LPHNPs) for the topical delivery of curcumin which can be a potential approach for mitigating psoriasis. Methods: Curcumin-loaded LPHNPs were prepared by the emulsification solvent evaporation method and characterized. The optimized Curcumin-loaded LPHNPs (DLN-3) were further incorporated into 2% Carbopol 940 gels and evaluated for its therapeutic efficacy in the Imiquimod (IMQ)-induced psoriasis rat model. Results: The average particle size, polydispersity index, zeta potential, drug entrapment and loading efficiency for DLN-3 were found to be 200.9 nm, 0.342,-28.3 mV, 87.40±0.99% and 4.57±0.04%, respectively. FT-IR, DSC and XRD studies confirmed that all the components used for the formulation are compatible with each other, whereas SEM and TEM analysis affirmed the spherical shape of LPHNPs with a smooth surface. The in vitro drug release studies suggest that curcumin was released from the LPHNPs in a sustained manner over a period of 24 h via super case II transport mechanism. Results of in vitro skin permeation study revealed that 38.39±2.67% of curcumin permeated at 12 h across excised pig ear skin with a permeation flux of 18.74±3.59 µg/cm2/h. Further, in vivo evaluation and histopathological studies demonstrated that NLHG-1 hydrogels showed better therapeutic efficacy against the psoriatic skin lesions than the standard marketed gels. Conclusion: These results suggest that the developed LPHNPs have a superior ability to improve the skin penetration or accumulation of DLN-3 within psoriatic skin and offer a potential delivery system for the management of psoriasis.